2009
DOI: 10.1111/j.1525-1594.2009.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time Monitoring of Force Response Measured in Mechanically Stimulated Tissue‐Engineered Cartilage

Abstract: Mechanical stimulation improves tissue-engineered cartilage development both in terms of biochemical composition and structural properties. However, the link between the compositional changes attributed to mechanical stimulation and the changing structural properties of the engineered cartilage is poorly understood. We hypothesize that transient events associated with construct stiffening can be documented and used to understand milestones in construct development. To do this, we designed and built a mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Results from bioreactor studies show increases in production of ECM molecules, cell proliferation, and mechanical properties [87,88]. For example, PGA scaffolds in a perfusion system showed increases in both DNA and GAG content compared to controls [89].…”
Section: Dynamic Culture Systemsmentioning
confidence: 93%
“…Results from bioreactor studies show increases in production of ECM molecules, cell proliferation, and mechanical properties [87,88]. For example, PGA scaffolds in a perfusion system showed increases in both DNA and GAG content compared to controls [89].…”
Section: Dynamic Culture Systemsmentioning
confidence: 93%
“…Numerous short-and long-term studies have shown that dynamic compression protocols, at moderate levels (2%-15% strain; 0.5-1 MPa) spanning a wide range of physiological frequencies (0.01-1.0 Hz) can modulate chondrocyte viability, gene expression, and biosynthesis of various extracellular matrix molecules. [44][45][46] Therefore, the force range of our device is 0.5 to 30 N and the frequency range is 0.01 to 1 Hz; both the force range and loading profiles are easily adjustable and definable by the user.…”
Section: Brady Et Almentioning
confidence: 99%
“…For standard specimen diameters of 4-8 mm, these loads correspond to stresses of 2-500 kPa, and cover the spectrum of stimulation magnitudes and frequencies normally applied in cartilage TE studies. 17,22 This level of loading accuracy for a batch-testing bioreactor is uncommon, and differentiates the MATE from contemporary bioreactors that load multiple TE constructs. In an independent review of 205 peer-reviewed articles that applied compressive loads to TE constructs, 84% displaced multiple specimens with a single mechanoelectric actuator, and 95% did not report accounting for alterations in specimen thickness during culture.…”
Section: ) (B)mentioning
confidence: 99%
“…Static loads were applied at low magnitudes (0.1-1.0 N) and high magnitudes (1.0-10.0 N) to represent the forces commonly used to compress soft hydrogels and mature cartilage, respectively. 17,22 For dynamic testing, a linear spring (Lee Spring, Brooklyn, NY; 10 N/mm) was loaded with variable sinusoidal amplitudes (0.1-10.0 N) and frequencies (1, 10 Hz). The spring was preloaded to 0.2 N before applying oscillations.…”
Section: Mechanical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation